2016
DOI: 10.1557/jmr.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of hardness and elastic modulus in BaFe2As2 lamellar-like material

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…The strain-direction dependence of the T c for P-doped Ba-122 single crystals showed that the change in T c is the smallest for [100] direction compared to [110] and [001] directions. 20 A similar trend is expected for Co-doped Ba-122, although the doping element differs from P. On the assumption that the Young modulus (E 100 ) of Co-doped Ba-122 is 55 GPa, 21 the respective tensile and compressive stress values are calculated as 9.9×10 −3 GPa and −1.65 × 10 −2 GPa using Hooke's law. Accordingly, the uniaxial pressure derivative of the offset T c approximates dT c /dp 100 = −4 K/GPa, which is in good agreement with the results for Ba(Fe 0.926 Co 0.074 ) 2 As 2 single crystals obtained from the specific heat and thermal expansion data using the Ehrenfest relation.…”
supporting
confidence: 58%
“…The strain-direction dependence of the T c for P-doped Ba-122 single crystals showed that the change in T c is the smallest for [100] direction compared to [110] and [001] directions. 20 A similar trend is expected for Co-doped Ba-122, although the doping element differs from P. On the assumption that the Young modulus (E 100 ) of Co-doped Ba-122 is 55 GPa, 21 the respective tensile and compressive stress values are calculated as 9.9×10 −3 GPa and −1.65 × 10 −2 GPa using Hooke's law. Accordingly, the uniaxial pressure derivative of the offset T c approximates dT c /dp 100 = −4 K/GPa, which is in good agreement with the results for Ba(Fe 0.926 Co 0.074 ) 2 As 2 single crystals obtained from the specific heat and thermal expansion data using the Ehrenfest relation.…”
supporting
confidence: 58%
“…The hardness of the 211 phase is 14 + 2 GPa, while it is about 10-11 GPa for the pure 123 phase. Values of the single crystal with lamellar-like structure, with a small size of approximately 1 mm and 20 μm thick (observed at the lamellar edges), were lower than those of the melt textured samples, explained by the specific deformation features of lamellar-like structures, as discussed previously in this report and in 21,22 .…”
Section: Resultssupporting
confidence: 70%
“…Nevertheless, others factors may originate the variation observed in hardness with penetration depth, as outermost plastic deformation layers produced by polishing, microcracking in adjacent lamellae, or the crushing of inner pores. Actually, such decrease was small compared to those observed in other lamellar-like single crystals 21,22 (it is in the order of the error bars), having little influence in the measurements.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Out of the four independent elastic constants 43 , C 11 , C 12 , and C 33 have recently been reported by a resonant ultrasound spectroscopy (RUS) study 30 for 3.7% Co doped BaFe 2 As 2 as a function of temperature. We here determine the missing C 13 by assuming an equal in-and out-of-plane Young's modulus (as suggested by a recent instrumented indentation experiment 44 ) and arrive at Using this tensor as an estimation for the shear-free mechanical properties of 2.5% Co doped BaFe 2 As 2 in the vicinity of its structural transition, it is straightforward to calculate the symmetry decomposed strain fields from the measured hydrostatic pressure and ǫ xx for the two sets of experiments.…”
Section: Appendix C: Finite Element Simulationsmentioning
confidence: 99%